2018
DOI: 10.1039/c8cc05030a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic regeneration of a Th–H bond from a Th–O bond through a mild and chemoselective carbonyl hydroboration

Abstract: Here we present an unprecedented chemoselective hydroboration for aldehydes and ketones catalysed by actinides. The reaction features a very low catalyst loading (0.1-0.004 mol%) and quantitative product formation in less than 15 minutes, at room temperature. Thermodynamic and kinetic studies including stoichiometric and labeling studies with deuterated pinacolborane allow us to propose a plausible mechanism for this remarkable catalytic regeneration of a Th-H bond via carbonyl hydroboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
(1 reference statement)
3
20
0
Order By: Relevance
“…Colorless oil; 1 H NMR (400 MHz, CDCl 3 ) δ 7.44 (dd, J = 8.4, 1.8 Hz, 2H), 7.23–7.18 (m, 2H), 4.86 (s, 2H), 1.25 (s, 12H); 13 C NMR (100 MHz, CDCl 3 ) δ 138.30, 131.48, 128.50, 121.30, 83.22, 66.06, 24.70. NMR data were in accordance with reported literature 12 …”
Section: Methodssupporting
confidence: 88%
“…Colorless oil; 1 H NMR (400 MHz, CDCl 3 ) δ 7.44 (dd, J = 8.4, 1.8 Hz, 2H), 7.23–7.18 (m, 2H), 4.86 (s, 2H), 1.25 (s, 12H); 13 C NMR (100 MHz, CDCl 3 ) δ 138.30, 131.48, 128.50, 121.30, 83.22, 66.06, 24.70. NMR data were in accordance with reported literature 12 …”
Section: Methodssupporting
confidence: 88%
“…In 2018, the Eisen group reported an unprecedented chemoselective hydroboration of ketones and aldehydes catalyzed by the actinide complexes 41 and 42 (Figure 4). 46 This study not only demonstrated again the feasibility of transforming oxygen-containing substrates, but also investigated the possibility of regenerating an An-H bond from a thermodynamically stable An-O bond. In the presence of 0.1 mol% to 0.004 mol% of the complexes 41 and 42, carbonyl compounds were hydroborated with HBpin in almost quantitative conversions in 15 minutes, and with TOFs as high as 100,000 h -1 , which is highest value ever reported for a hydroboration process.…”
Section: Scheme 15 Proposed Mechanism For Ester Hydroborationmentioning
confidence: 93%
“…The progress of the reactions were monitored by 1 H NMR spectroscopy. The products were identified by 1 H NMR and 13 C spectroscopy and the chemical shifts were compared with previously reported literature data , …”
Section: Methodsmentioning
confidence: 99%
“…The hydroboration of C=O bonds is particularly impressive and it is strengthening its prestige as one of the utmost useful and most widely used reactions for the pharmaceutical industry . Carbonyl hydroboration catalysts include alkaline earth metals,, transition metals, group 13 metal catalysts, lanthanide, actinides, and other unique and sophisticated systems . In addition to the hydroboration of C=O bonds, the selective monohydroboration of carbodiimides to produce amidinates is also of great interest, since these systems play an important role in coordination chemistry …”
Section: Introductionmentioning
confidence: 99%